Design and Implementation of Automatic Wheat Mower Based on Smart Sensor Fed by a Photovoltaic - Esen, Hikmet; Kapicioglu, Abdullah; Ozsolak, Onur (Hindawi Ltd, 2016)
The biggest problems of our time are environmental pollution and the reduction of fossil fuel resources. In recent years, photovoltaic (PV) has started to be used efficiently in order to produce electrical energy from solar energy throughout the world. In this study, a wheat mover machine taking its energy with PV technology transformation from the sun was designed supported by smart sensors. The designed vehicle was tested in two wheat fields in Sivas in Turkey. It was seen that daily average sunshine rates were not lower than 700 Watt/m(2) during the testing dates and tune. The amounts of electrical charge used to mow 5 m(2) and 50 m(2) areas are obtained as 500 mAh and 3395 mAh, respectively. Also maximum power is calculated from used PV panel as 26.15 Watt during the day of the experiments. The range of solar radiation intensity is found 4.5 kWh/m(2)/day at the studied kWh which was $0.140 USD on the date of November 2015. his system is 94.5% more economic than conventional mowers over an area of 1000 m(2).
Keywords: Multipurpose Electric Vehicle; Battery Power-Systems